2017
DOI: 10.1097/qai.0000000000001251
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of HIV Pre-Exposure Prophylaxis (PrEP) in a National Cohort of Gay and Bisexual Men in the United States

Abstract: Objectives The HIV care cascade provides milestones to track the progress of HIV-positive people from seroconversion through viral suppression. We propose a Motivational PrEP Cascade involving five stages based upon the Transtheoretical Model of Change. Methods We analyzed data from 995 men in One Thousand Strong, a longitudinal study of a national panel of HIV-negative gay and bisexual men in the United States. Results Nearly all (89%) participants were sexually active in the past 3 months, and 65% met CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
224
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(243 citation statements)
references
References 32 publications
7
224
0
3
Order By: Relevance
“…Previous studies have also shown similar discrepancies between PrEP interest and uptake among Black MSM [7] with overall low uptake reported (2.5–18%) [7, 24, 27–30]. In their ‘Motivational PrEP Cascade’ based on the Transtheoretical Model of Change, Parsons et al show that many MSM are lost in the pre-contemplative (unwilling to take PrEP or believe they were appropriate PrEP candidates) or contemplative (willing to take PrEP but without real plans to start) stages of behavior change [31]. Our baseline PrEP interest survey suggests that initial barriers to willingness may include self-assessed low risk behavior and the requirement for daily adherence, which is consistent with data from prior studies [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown similar discrepancies between PrEP interest and uptake among Black MSM [7] with overall low uptake reported (2.5–18%) [7, 24, 27–30]. In their ‘Motivational PrEP Cascade’ based on the Transtheoretical Model of Change, Parsons et al show that many MSM are lost in the pre-contemplative (unwilling to take PrEP or believe they were appropriate PrEP candidates) or contemplative (willing to take PrEP but without real plans to start) stages of behavior change [31]. Our baseline PrEP interest survey suggests that initial barriers to willingness may include self-assessed low risk behavior and the requirement for daily adherence, which is consistent with data from prior studies [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…However, other biomedical prevention techniques such as pre‐exposure prophylaxis (PrEP) have had limited uptake over time despite both strong public health endorsements and relatively high initial acceptability 15, 16, 17, 18, 19, 20. Some barriers to PrEP uptake that have been noted, such as inaccurate knowledge and risk perception 21 as well as community norms about condom use 22, 23, may also important to consider as part of the implementation and scale‐up of TasP messaging.…”
Section: Introductionmentioning
confidence: 99%
“…5 The majority of HIV-positive MSM remain sexually active after HIV diagnosis, 6;7 and approximately 40% report engaging in condomless sex. 8;9 While newly promoted biomedical HIV prevention strategies, entailing pre-exposure prophylaxis (PrEP) 10 and “treatment-as-prevention” (TasP), 11 can substantially decrease the likelihood of sexually-based HIV acquisition and transmission, even when condoms are not used, 10-15 rates of PrEP uptake among MSM are low, 16;17 and marked gaps in the HIV treatment cascade remain, such that only an estimated 16-34% of HIV-positive MSM in the US have attained an undetectable HIV viral load. 18 As a result, a sizable number of HIV-negative and HIV-positive MSM remain “biologically unprotected” from acquiring or transmitting HIV, respectively.…”
Section: Introductionmentioning
confidence: 99%